Organization administration and sport technology - Rokade, P.R
There are some huge differences between the sport of a few decades ago and the sport of today. One of the things that have seen many changes is sports management. Technology has meant that managers now carry out their work in many different ways. It has improved communication, documentation and the ability to analyze performance. Thirty years ago there were no personal computers, cell phones, and digital cameras and sports management professionals had to do a lot more leg work in order to be successful. With professional sports teams and organizations technology affects just about every position of a sports management professional and is extremely helpful in them being successful in that position. This is the perfect reference book for any course in sports management, sports administration or sports organization. Students, teachers and all those involved with the sports field will fine this book useful.